Deserters on the atopic march: Risk factors, immune profile and clinical outcomes of food sensitized–tolerant infants. Issue 6 (17th January 2020) - Gray, Lawrence E. K.; Ponsonby, Anne‐Louise; Collier, Fiona; O'Hely, Martin; Sly, Peter D.; Ranganathan, Sarath; Tang, Mimi L. K.; Carlin, John B.; Saffery, Richard; Vuillermin, Peter J.; ,
Abstract: Background: A few studies have investigated the antecedents and outcomes of infants who demonstrate IgE sensitization to foods that they clinically tolerate. Improved understanding of this sensitized‐tolerant phenotype may inform strategies for the prevention of food allergy. Methods: In an Australian birth cohort (n = 1074), assembled using an unselected antenatal sampling frame, participants were categorized as nonsensitized (NS), sensitizedtolerant (ST), or food allergic (FA) based on skin prick testing and food challenge at 12 months of age. Environmental exposures were recorded throughout. Cord blood regulatory T‐cell populations were measured at birth. Subsequent childhood allergic disease was assessed by parent report, clinical examination, and repeat skin prick testing. Results: The covariates of interest varied between NS (n = 698), ST (n = 27), and FA (n = 61) groups as follows, suggesting that across these measures, the ST group was more similar to the NS than the FA group: family history of eczema NS 44.6%, ST. 44.6%, FA 65.6%; pet ownership at 12 months: NS 71.5%, ST 81.5%, FA 45.8%; eczema during the first 12 months: NS 19%, ST 32%, FA 64%; and aeroallergen sensitization at 4 years: NS 19.1%, ST 28.6%, FA 44.4%. At birth, a higher proportion of activated regulatory T cells was associated with ST (OR = 2.89, 95% CI 1.03‐8.16, P = .045). Conclusion: Food‐sensitized‐tolerance in infancy appears to be associated with a similar pattern of exposures, immunity, and outcomes to nonsensitized infants. In addition, we found some evidence that an elevated proportion of activated regulatory T cells at birth was specific to the sensitized‐tolerant infants, which may be relevant to suppression of clinical disease. Abstract : Food‐sensitized tolerance in infancy appears to be associated with a similar pattern of exposures, immunity, and outcomes to nonsensitized infants. Compared to infants with clinical food allergy, both sensitized‐tolerant and nonsensitized infants were more likely to be exposed to pets in infancy, had less eczema during the first 12 months and less aeroallergen sensitization at 4 years of age. A lower proportion of naïve regulatory T cells at birth was observed among food allergic infants than nonsensitized infants. Abbreviations BIS, Barwon Infant Study; SPT, skin prick test; Treg, regulatory T cell